Deep-Blue Thermally Activated Delayed Fluorescence Polymers for Nondoped Solution-Processed Organic Light-Emitting Diodes - Li, Chensen; Ren, Zhongjie; Sun, Xiaoli; Li, Huihui; Yan, Shouke (Macromolecules, 2019)
The exploitation of deep-blue polymeric emitters is of great importance for the application of solution-processed organic light-emitting diodes (OLEDs) in full color display. The highly efficient deep-blue thermally activated delayed fluorescence (TADF) polymers are rarely reported up to now. Herein, we developed a series of deep-blue TADF polymers to fabricate highly efficient nondoped solution-processed OLEDs. By incorporating appropriate host with high triplet energy and deep-blue emitter with high fluorescent efficiency, the polymers are endowed with distinct TADF features. Using these deep-blue polymeric emitters, the nondoped single polymer based OLEDs achieve a maximum external quantum efficiency of 5.3% with the Commission Internationale de L’Eclairage (CIE) coordinates of (0.15, 0.09), which represents the state-of-the-art device performance for the TADF-based deep-blue polymer light-emitting diodes (PLEDs).